3. Institutional Support Required To Integrate Small Farmers For Livestock Commodity Value Chain-A Case Study - Taliyil P Sethumadhavan (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
Recent reports reveal that in the globalised era farming will move towards meat and milk production from traditional rice and grain agriculture in line with the changing consumer tastes. The joint report by Food and Agriculture Organization in Rome and the Paris based organisation for Economic Cooperation and Development (OECD) of 34 leading world economies contained price and production forecasts to 2023 revealed that world meat production will have gone up by 58 million tones with developing countries making up 80 percent of increase. Report highlights that livestock production is projected to grow at higher rates than crop production. Moreover animal protein sources are easiest way through which protein malnutrition can be corrected easily. Since the commodity value of livestock products are high when compared to agriculture commodities in the coming years livestock products will the focus area for augmenting GDP in Agriculture sector. So institutional support are required for increasing production, productivity, food security, food safety, knowledge dissemination and services to achieve these objectives.